Enhanced thermal conductivity of Cu Grafted graphene-C2H6O2 based nanofluids by laser ablation for potential application as coolants in data centers - M. Aligholami; M. Akbari; R. Morad; T. M. Moodley; M. Adebisi; T. Fakude; S. Heshmatian; M. Maaza (Scientific Reports)
Abstract This contribution reports for the first time on the enhancement of the thermal conductivity of graphene grafted with Cu nanoparticles—ethylene glycol-based nanofluid (with a relatively low Cu volume concentration of about 0.3% & without any dispersant). This latter nanofluid engineered by Pulsed Laser Ablation in Liquid Solution (LLSI-PLAL) exhibited a significant thermal conductivity enhancement of 12.6% conjugated to a noteworthy time stability of at least 3 to 4 weeks without any additional dispersing agent of any sort. This latter time stability corroborates with Density Functional Theory as well as the Molecular Dynamic theoretical investigations. These latter showed that the binding affinity of Cu nanoparticles onto graphene nanosheets is far superior relative to those of Au or Ag nanoparticles onto graphene (bridge adsorption energies of -0.58, -0.24, and -0.5 eV for Cu, Ag & Au, respectively). Cost-wise, compared to previously validated Au-Graphene/EG and Ag-Graphene/EG, the reported Cu-Graphene/EG nanofluids would be more suitable for mass production in view of their cost-effectiveness, especially in mass technological applications, including but not limited to heat removal & cooling in data centers.